METODE PEMBELAJARAN BERBASIS GAME UNTUK MENINGKATKAN KETRAMPILAN MEMBACA DAN MENULIS AKSARA JAWA - Whinny Qori Fatima; Livia Khairunisa; Budi Prihatminingtyas (Universitas Tribhuwana Tunggadewi, 2020)
The purpose of this study is to find out how effective game-based learning is for improving Javanese script reading and writing skills. This research method is qualitative with the sources of data from this study are caregivers, foster children, and documents. The target in this study was the Al-Maun orphanage located on Margo Noyo street, Ngajum Village, Ngajum District, Malang Regency, East Java Province, Indonesia. Data collection techniques used were interviews, observation, documentation and tests. The data analysis technique used is an interactive model. From the results of this study it can be concluded that the game-based learning method is very effective in improving the ability to read and write Javanese script among children. Judging from the results the average value of children - children increased and only 8% are below the average (75).